Simultaneous production of bioelectricity and biogas from chicken droppings and dairy industry wastewater employing bioelectrochemical system. (15th November 2019) - Fazal, Tahir; Saif ur Rehman, Muhammad; Mushtaq, Azeem; Hafeez, Ainy; Javed, Fahed; Aslam, Muhammad; Fatima, Masoom; Faisal, Abrar; Iqbal, Javed; Rehman, Fahad; Farooq, Robina
Graphical abstract: Highlights: Self-sustainable bioelectrochemical system is developed to produce biogas instead of hydrogen. Anaerobic co-digestion of dairy milk industry wastewater along with chicken droppings is investigated. Simultaneously generation of biogas and bioelectricity. Utilization of self-produced electricity as cathodic potential to enhance biogas generation. Abstract: Bioelectrochemical systems (BESs) provide an opportunity for COD removal in wastewater while generating electricity simultaneously. Previous studies have shown simultaneously wastewater treatment and hydrogen gas generation through catalytic reactions of microorganism under anaerobic condition. However, in this study, BES is developed to produce biogas instead of hydrogen from different compositions of wastewater while generating electricity. Dual chamber is designed and kept anaerobically over a period of 20 days in a temperature controlled (35 °C) anaerobic chamber. Wastewater of dairy milk industry is used along with chicken droppings as an organic substrate. BES is operated using three different substrate compositions designated as BES-A, BES-B and BES-C. The performance of BES having microbial bio-anode based on a hydrogen-philic methanogenic culture, capable of reducing CO2 and H + into CH4 by gaining of electrons from cathode is investigated. The highest volume production rate of biogas upto 65 cm 3 /day in BES-A is obtained as compared to 45 and 37.5 cm 3 /day in BES-B and BES-C, respectively. Cyclic voltammetry analysis showed that the range of open circuit voltage (−800 to −1225 mV) is highest in BES-A due to the bio-catalytic activities. Moreover, the maximum volume of biogas, electric current, open circuit voltage, current density, power density and COD removal are obtained as 730 cm 3, 0.57 mA, −1225 mV, 0.035 mA/cm 2 and 43.29 mW/cm 2 and 74.19%, respectively in BES-A, after 12 days of hydrolytic retention time. The electricity produced by the cell itself is utilized as cathodic potential for enhancing the efficiency of biogas production. The required potential for the production of biogas is −1400 to −1800 mV. However, the designed BES itself generated −800 to –1225 mV, out of which only −600 mV is supplied through the external source of battery to maintain the required voltage for biogas production. The extra voltage of ∼600 mV can be generated from produced biogas to develop a self-sustained system for wastewater treatment.